COMPOSITION, CONTENT AND HISTORY OF SHARAFUDDIN ALI YAZDI'S "ZAFARNOMA" - Erimmatova Gulnoza (Galaxy International Interdisciplinary Research Journal, 2021)
This article is about the composition, content and history of Sharafuddin Ali Yazdi's "Zafarnoma" and provides information about the general concepts and their place in our history.